Gestão democrática na educação infantil para crianças com Transtorno do Espectro Autista - Mendonça, Luana Paz (Brasil, 2023)
The objective of the research is to understand a management in early childhood education more democratic and quality aimed at children with Autism Spectrum Disorder (ASD). The study was based on the main theorists such as: Cunha (2020), Libâneo (2002), Mantoan and Santos (2010), Paro (2017), Romão (1997), Sassaki (1997), Schmidt (2013). The research is a bibliographic research with a qualitative approach. The research was based on the following databases: Scielo, Portal da Capes, Repositories of Public and Private Universities, Scopus and google scholar. The collection of the UFAM library was also consulted. The Federal Constitution was a milestone for public inclusion policies, thus opening space for the creation of social inclusion policies. The school management when it involves atypical students go through a modification, in order to make a quality management that includes all, before that it becomes challenging to analyze strategies, verify the specificities of each student, their reality, because of this the role the manager is indispensable for all these challenges to be effective, it is he who guides, Coordinates and evaluates the progress of the school's pedagogical work. Finally, it is also considered important the interest of the institutions so that they can improve their pedagogical practices, aiming at an inclusive and democratic school that seek forms of joint intervention, fully performing in its mediating character, assuming in an egalitarian way to meet the needs of each student.